The Simian Virus 40 Small-t and Large-T Antigens Jointly Regulate Cell Cycle Reentry in Human Fibroblasts - Porrás, Analía (American Society for Microbiology, 1999)
Focus formation in human diploid fibroblasts (HDF cells) is known to require both the simian virus 40 (SV40) large-T and small-t antigens. Similarly, both SV40 proteins were required to stimulate confluent, density-arrested HDF cells to reenter the cell cycle. This study used defective recombinant adenoviruses to examine the roles of the individual SV40 proteins in altering specific steps in the cell cycle. Small-t antigen and, to a lesser extent, large-T antigen increased the level of the S phase cyclin cyclin A but without increasing the activity of associated cyclin kinases unless the two SV40 proteins were coexpressed. The absence of kinase activity reflected the presence in density-arrested cells of high levels of the cyclin-dependent kinase inhibitors p21(WAF1) and p27(KIP1). We report here that expression of SV40 large-T antigen reduced levels of p21(WAF1), while expression of small-t antigen was required to decrease p27(KIP1). The separate effects of large-T and small-t antigens on these two inhibitors may explain the joint requirement for the two proteins to drive cell cycle reentry of HDF cells and ultimately transform these cells.